A decolonial critique in the context of a university oriented towards south-south cooperation: an institutional ethnographic study (Revista Contexto & Educação, 2025)
The research aims to understand a university project oriented towards South-South cooperation, captured through the lens of institutional practices in tension in the light of (de)coloniality. The critical institutional ethnographic method was considered, which produced an understanding based on three dimensions: (i) a scenario of reaffirmation of the institutional mission until 2014; (ii) a propositional agenda in the field of regional integration from 2014 onwards; (iii) reference to the conceptions of ‘excellence’, ‘performance’ and ‘quality’ triggered by the opening of stricto sensu postgraduate courses and an emphasis on the logic of student permanence after 2016. It discusses the conceptual, theoretical and normative basis situated in a documental institutionality, to understand what is intended utilizing the concepts ‘excellence’, ‘performance’ and ‘quality’, from the perspective of building decolonial agendas. The institutional practices described ethnographically, based on a critical decolonial perspective, broaden a 'reading' of the institutional challenges, giving rise to considerations about the unfolding of their practices from readings related to ‘neo-racism’, ‘nationalism’ and ‘patriotism’.
Keywords: University Practices; Decoloniality; Institutional Tensions